1969
DOI: 10.1084/jem.130.3.659
|View full text |Cite
|
Sign up to set email alerts
|

Small Intestinal Mucosal Cell Proliferation and Bacterial Flora in the Conventionalization of the Germfree Mouse

Abstract: Intestinal mucosal cells, originating in the crypts, migrate up the villi of the small intestine and slough off into the lumen (1, 2). Studies of the kinetics of these events have revealed a differential rate of cellular renewal between the intestinal mucosal cells of germfree animals and those of conventional animals (3, 4). The time for migration of the mucosal cells from the crypt to villus tip is twice as long in the germfree animal (3, 4). The absence of intestinal bacterial flora in the germfree animal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

1975
1975
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 22 publications
(24 reference statements)
3
38
0
1
Order By: Relevance
“…A reduced proliferation rate and lower expression of antimicrobial genes of IECs was observed in GF and broad-spectrum antibiotictreated mice. 37,38 These data suggest that the gut microbiota can condition the immunoregulatory roles of IECs by regulating the expression of antimicrobial factors.…”
Section: Gut Microbiota and Immune Homeostasismentioning
confidence: 98%
“…A reduced proliferation rate and lower expression of antimicrobial genes of IECs was observed in GF and broad-spectrum antibiotictreated mice. 37,38 These data suggest that the gut microbiota can condition the immunoregulatory roles of IECs by regulating the expression of antimicrobial factors.…”
Section: Gut Microbiota and Immune Homeostasismentioning
confidence: 98%
“…The microflora of the alimentary canal had no effect on the true digestibilities of proteins but were able to modify the route of excretion of undigested nitrogenous compounds reaching the lower gut (Salter and Coates 1971;Salter and Fulford 1974;Salter et al 1974). However, according to Erbersdobler and Riedel (1912) Work with mice has shown that intestinal microflora alter cell renewal rates in the ileum (Abrams et al 1963), duodenal crypts (Lesher et al 1964) and small intestine (Khoury et al 1969 Yoshida et al (1965), Yoshida and Morimoto (1966,1970) and Squibb (1971 (1961) found the AME values of oats to increase with bushel weight; this was confirmed by Sibbald and Slinger (1963a), Sibbald and Price (1976a) but not by Salo (1978) whose AME values were calculated from chemical composition. The TME values of oats were related to bulk density (Sibbald and Price 1977a) as were ADE values measured with mice (Christison and Bell 1975 (Hochstetler and Scott 1975 Carpenter and Clegg (1956), Bolton (1962b) and Sibbald et al.…”
Section: Control Of Feed Intakementioning
confidence: 99%
“…(Stragand and Hagemann, 1977 (Bayle, 1969 ;Coates et ol., 1969 ;Hiller and Schoen, 1971 Rolls et al,1975 ;mouse : Abrams et al,1963 ;Lesher et al,1964 ;Khoury et al, 1969 ;Ranken, Wilson and Bealmer, 1971 ;Mastromarino and Wilson, 1976 ;rat : Guenet et al, 1970 ;Galjaard et at., 1972 ;Meslin et al, 1974) or partial (Meslin, Sac- …”
Section: Introductionmentioning
confidence: 99%